Reconstruct the Class Assessment Strategy: Promoting the 21st-Century Learning - Rosidin, Undang; haryanti, Novi; Lora, Haditya Aprita; Viyanti, Viyanti (Universitas Islam Negeri Raden Intan Lampung, 2020)
The purpose of this research is to reconstruct the class assessment to promote 21st-century learning. The meaning of reconstructing class assessment is the advanced assessment that can realize the purpose of 21st-century learning which is the ability of argumentation, critical, and creative thinking skills. The advanced assessment in this research used the model of Argument-Driven Inquiry (ADI). This research is a quasi-experimental study that uses a pre-test post-test non-equivalent control group design. The research population is 12th-grade students of senior high school on Bandar Lampung. Based on data analysis, it was revealed that the classroom assessment strategy with continuous assessment using the ADI model can be used as a reference to be able to practice 21st-century life skills including argumentation, critical thinking, and creative skills.